Modification of stainless steel based on synergistic of low-energy high-intensity ion implantation and high-current electron beam impact on the surface layer; Journal of Physics: Conference Series; Vol. 2064 : Gas Discharge Plasmas and Their Applications (GDP 2021) - Ryabchikov A. I. Aleksandr Ilyich; Korneva O. S. Olga Sergeevna; Sivin D. O. Denis Olegovich; Ivanova A. I. Anna Ivanovna; Lopatin I. V. Iljya Viktorovich; Bozhko I. A. Irina Aleksandrovna (2021, 2021)
Title screen